2011
DOI: 10.1002/pts.961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Packaging Liners on Cooling Rate and Quality Attributes of Table Grape (cv. Regal Seedless)

Abstract: Table grapes are commonly packed in multi‐layered packages consisting of cardboard carton, plastic liners and carry bag/pouch to maintain product quality along the cold chain. Each liner is characterized by the number and the size of perforations, which influence the environmental conditions around the produce inside the package. This study investigated the effects of different carton liners on the cooling rate and quality attributes of ‘Regal Seedless’ table grapes. Fruit quality attributes measured include w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…A comparison of the effect of types of liners with Regal Seedless showed that unperforated liners in an RH of 100% maintain lower rachis browning as compared with those in perforated liners with an RH of about 92% (Ngcobo et al . ), but SO 2 injuries were higher in the closed liners. Interestingly, the liner with multiple micro‐perforations caused the lowest pressure drop in a wind tunnel, and its rachis score was better than that for liners with a high degree of perforation (Ngcobo et al .…”
Section: Packaging During Cold Storage and Shelf‐lifementioning
confidence: 84%
See 1 more Smart Citation
“…A comparison of the effect of types of liners with Regal Seedless showed that unperforated liners in an RH of 100% maintain lower rachis browning as compared with those in perforated liners with an RH of about 92% (Ngcobo et al . ), but SO 2 injuries were higher in the closed liners. Interestingly, the liner with multiple micro‐perforations caused the lowest pressure drop in a wind tunnel, and its rachis score was better than that for liners with a high degree of perforation (Ngcobo et al .…”
Section: Packaging During Cold Storage and Shelf‐lifementioning
confidence: 84%
“…Rachis dehydration is classified according to another five‐point index based on the degree of shrivelling of thin or thick rachises (Ngcobo et al . ), but application of this type of scale appears to require a good deal of training.…”
Section: Methods To Measure Rachis Browningmentioning
confidence: 99%
“…For example, 8 hours of RC for carnations was performed without packages or with open boxes . Additionally, proper packaging was also investigated for table grapes which were only suitable for air‐based precooling . In recent years, detailed characterization of airflow, heat transfer, and mass transfer during RC could be performed by experimental measurements .…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, proper packaging was also investigated for table grapes which were only suitable for air-based precooling. 11 In recent years, detailed characterization of airflow, heat transfer, and mass transfer during RC could be performed by experimental measurements. 12 With the help of these experimental methods, simplified heat and mass transfer models by solving system of linear equations were developed to predict the performances of RC.…”
Section: Introductionmentioning
confidence: 99%
“…However, table grapes deteriorate easily by pathogen infection due to their characteristics of being soft and having a high moisture content, which lead to the quality and safety issues of table grapes that have received worldwide attention [1,2]. Cold chain logistics is an effective measure to ensure that table grapes are stored in a low temperature environment all of the time by using artificial refrigeration technology when they are in various links, such as processing, storage, transportation, sale, etc., and to reduce the quality losses of table grapes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%